2024 IFFAS Award for Excellence Winner: Minimally Invasive Chevron Akin for Hallux Valgus Surgery: A Prospective Observational Study with Mean 6.7 year Follow Up - Oliver Townsend BSc (Hons), MBBS, MRCS; Niall Hill; Adam Reaney BSc (Hons), MRCPod, LLCM, ARSM; Togay Koç MBBS, MSc, FRCS (TO); Thomas L. Lewis BSc (Hons) MBChB (Hons) FRCS (Tr & Orth) MFSTEd; David Gordon MB ChB, MRCS, MD, FRCS (Tr & Orth) (Foot & Ankle Orthopaedics)
Category: Bunion Introduction/Purpose: Minimally invasive chevron and Akin (MICA) osteotomy surgery has become an established technique for correction of hallux valgus deformities. As a relatively new technique, however, long-term follow-up data is limited in the literature to 2-3 years. The purpose of this study is to assess a large cohort of patients undergoing MICA with minimum 5 year follow up, to evaluate the longer-term results of this procedure, using validated patient reported outcome measures (PROMs). Methods: 5-year PROM data was prospectively collected from 101 patients who underwent 147 primary MICA osteotomies between July 2014 and April 2018, performed by a single surgeon. Primary clinical outcome measures collected included visual analogue scale for pain (VAS-pain), Manchester-Oxford Foot Questionnaire (MOXFQ) and EuroQol-5 Dimensions (EQ-5D). Data were collected pre-operatively, at 2 years and after minimum 5 years. Statistical significance was set at p< 0.05. Results: 147 MICA osteotomies were performed on the feet of 101 patients (96 females, 5 males). Mean follow-up was 6.5 years (standard deviation [SD] 0.9 years), with all patients completing at least 5 years follow-up. The MOXFQ scores (mean ± SD) for all 147 feet improved for all domains: from 45.8 ± 21.9 preoperatively to 10.3 ± 16.8 postoperatively for Pain (p < 0.001), from 40.0 ± 23.8 to 9.1 ± 18.2 for Walking and Standing (p < 0.001), and from 48.5 ± 23.1 to 8.9 ± 18.5 for Social Interaction (p < 0.001). VAS-pain improved from 31.3 ± 22.6 preoperatively to 12.0 ± 20.6 postoperatively (p < 0.001). EQ-5D-5L Index improved from 0.739 ± 0.144 preoperatively to 0.900 ± 0.120 postoperatively (p < 0.001). Conclusion: This is the largest study reporting the patient reported outcomes following MICA with minimum five year follow up. This study demonstrates significant improvement in patient reported clinical outcome measures at mean 6.5 year follow up. MICA can be considered as an effective and long-lasting option for the correction of hallux valgus deformity.